Effect of concentration and steeping time on the antioxidant capacity of ginger tea - Tan, Dominique Viray (UP College of Home Economics, 2011)
ABSTRACT The purpose of this study was to evaluate the effects of concentration and steeping time on the antioxidant activity of hot aqueous extracts of ginger tea. The dried ginger was powdered and placed inside tea bags with dimensions 7cm x 6cm. Increasing amounts of powder, 5 g, 7 g and 9 g were used for each tea bag. These were steeped for 10 and 15 minutes for each concentration. The extracts were tested for total phenolic content using the Folin-Ciocalteu test, reducing power, DPPH radical scavenging activity and total antioxidant activity using the ferric thiocyanate method. Concentrations of 5% and 7% (w/v) with infusion time of 15 min exhibited high phenolic content, strong reducing power and strong radical scavenging activity. The varying ratio of tea bag size to amount of ginger powder contributed significantly to these results as this affects the rate of infusion and consequently the extraction of antioxidants. The 15-min steeping time proved to be more effective in extracting antioxidant compounds for both concentrations. All treatments showed high total antioxidant activities. Correlation studies yielded non-significant correlation between total phenolic content and the other parameters. The DPPH radical scavenging ability and reducing power showed no significant correlation with the total antioxidant activity.